Design of the Focus on Restaurant Engagement to Strengthen Health (FRESH) study: leveraging systems science to work with independently-owned restaurants to increase access to and promotion of healthful foods - Uriyoán Colón-Ramos; Emma C. Lewis; Anna Claire Tucker; Lisa Poirier; Chathurangi H. Pathiravasan; Michelle Estradé; Takeru Igusa; Julia A. Wolfson; Yeeli Mui; Veronica Vélez-Burgess; Audrey E. Thomas; Shuxian Hua; et al. (Frontiers in Public Health)
BackgroundHigh dietary quality can protect against diet-related chronic diseases. In the United States, racial and ethnic minorities and those with lower incomes consistently exhibit lower dietary quality. Independently-owned restaurants are a common prepared food source in minority low-income communities, but there are significant knowledge gaps on how to work with these restaurants to offer healthy food, due to underlying and dynamic complexities associated with providing healthy food options.MethodsThe Focus on Restaurant Engagement to Strengthen Health (FRESH) study addresses this complex problem by leveraging systems science approaches to work with independently-owned restaurants. FRESH has two interrelated objectives: (1) to test impact on regular customer dietary quality via a multisite cluster randomized controlled trial in two low-income urban areas (Baltimore and the Washington DC metropolitan area), and (2) to use systems science approaches to develop, parameterize, and calibrate a simulation model. The intervention is theory-and practice-based, comprising three phases: restaurant engagement, low-sugar beverages and healthy meals. The FRESH intervention will be implemented for 12 months in a total of 24 intervention and 24 comparison restaurants. The study is powered to detect a 5-point change in the Healthy Eating Index (HEI) score of regular customers, which would signify a meaningful shift toward healthier eating patterns.DiscussionThe FRESH study will test a novel, multilevel, multisite intervention that aims to improve access to healthier prepared food options among small, independently-owned restaurants located in under-resourced settings. The design of the FRESH intervention and its evaluation are described, as well as plans for the development of a system dynamics simulation model for policymakers and other stakeholders to virtually test future restaurant-based interventions.Clinical trial registrationhttps://clinicaltrials.gov, identifier, NCT05869149.